Comparative clinical outcomes of acenocoumarol versus direct oral anticoagulants (DOACs) and warfarin in patients with atrial fibrillation: real-world-evidence (SIESTA-A study) - Montero-Balosa, Ma Carmen; Limón-Mora, Juan A.; Leal-Atienza, Ana; García-Robredo, Beatriz; Sánchez-Villegas, Pablo; Isabel-Gómez, Rebeca; Aguado-Romeo, Ma José; Luque Romero, Luis Gabriel; Molina-López, Ma Teresa (Frontiers in Pharmacology, 2025)
ObjectiveThe aim of this study was to evaluate the effectiveness and safety of direct oral anticoagulants (DOACs: dabigatran, rivaroxaban, apixaban and edoxaban) and warfarin versus acenocoumarol in patients with atrial fibrillation under real-world clinical practice conditions.MethodsThis was a retrospective, real-world data-based study. The data source was the Andalusian Population Health Database. The study covered the period from January 2012 to December 2020. Effectiveness outcomes were defined as the identification of a first occurrence of ischaemic or bleeding events, or all-cause mortality. The statistical analysis included crude incidence analysis, survival models: Kaplan-Meier curves, propensity score matched pairs analysis, Fine-Gray model, and Cox regression analysis adjusted for possible confounding.ResultsA total of 150,949 patients were included. The mean age of the cohort was 74 years (48.2% female). The mean follow-up time was 3.3 years. The combined effectiveness endpoint of ischaemic events (transient ischaemic attack, systemic embolism, pulmonary embolism, or ischaemic stroke) showed the following results compared to acenocoumarol: warfarin (RR:1.06; 95%CI 0.93–1.22); dabigatran (RR:1.17; 95%CI 1.02–1.33); rivaroxaban (RR:1.15; 95%CI 1.05–1.26); apixaban (RR: 0.96; 95%CI 0.87–1.07) and edoxaban (RR: 1.10; 95%CI 0.79–1.51). Compared to acenocoumarol, the risk of all-cause mortality was lower for dabigatran, rivaroxaban and apixaban (RR:0.77; 95%CI 0.72–0.82; RR:0.79; 95%CI 0.76–0.83; RR:0.85; 95%CI 0.81–0.89, respectively) and higher for warfarin (RR:1.12; 95%CI 1.05–1.20). An increased risk of gastrointestinal bleeding was observed with dabigatran (RR:1.36; 95%CI 1.09–1.70) and a lower risk with rivaroxaban (RR:0.84; 95%CI 0.72–0.98). All 4 DOACs showed a lower risk of intracranial bleeding compared to acenocoumarol. Warfarin carried a higher risk of both gastrointestinal bleeding (RR:1.64; 95%CI 1.31–2.06) and intracranial bleeding (RR:1.61; 95%CI 1.22–2.13) compared to acenocoumarol. An unadjusted analysis of matched groups in a multivariate Cox regression analysis yielded similar results for combined effectiveness and safety outcomes compared to acenocoumarol.ConclusionAlthough DOACs were clearly associated with a lower risk of intracranial bleeding compared to acenocoumarol, our data did not reveal a significant reduction in thromboembolic events. Warfarin was found to be both less effective and less safe than acenocoumarol.